PENGARUH NON PERFORMING LOAN, CAPITAL ADEQUACY RATIO DAN LOAN TO DEPOSIT RATIO TERHADAP CADANGAN KERUGIAN PENURUNAN NILAI DENGAN KOMPETENSI KOMITE AUDIT SEBAGAI PEMODERASI (STUDI EMPIRIS PADA PERUSAHAAN PERBANKAN YANG TERDAFTAR TAHUN 2014-2018 DI BURSA EFEK INDONESIA) - Napisah, Napisah (GOING CONCERN : JURNAL RISET AKUNTANSI, 2020)
This study aims to examine the effect of non performing loan, capital adequacy ratio, and loan to deposit ratio on allowance for impairment losses with audit committee competencies as moderating variables on the public banking firms that listed in the Indonesia Stock Exchange for period 2014 to 2018. The independent variables of this study are non performing loan, capital adequacy ratio, and loan to deposit ratio, while the dependent variable in this study is allowance for impairment losses with audit committee competence as moderating variables. The method of analysis of this study is multiple regression analysis with moderating variables. This study uses purposive sampling method and get 20 public banking firms as the sample with 100 data observerd. The results of this study indicate that: (1) NPL significantly effect on CKPN; (2) CAR insignificant on CKPN; (3) LDR insignificant on CKPN; (4) KKA insignificanton CKPN; (5) NPL insignificant on CKPN while moderated by KKA; (6) CAR insignificant on CKPN while moderated by KKA; and (7) LDR insignificant on CKPN while moderated by KKA.